Peningkatan Proses Pembelajaran Tematik Terpadu dengan Model Number Head Together di Kelas IV SD - Wahyuni, Ocha Tri; Hamimah, Hamimah (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2022)
This research is backed by reality in the field that shows low student involvement in the learning process. The purpose of this study is to describe the use of Number Head Together model to enhance the integrated thematic learning process IN class IV of SDN 23 Ujung Gurun. This type of research is class action research using qualitative and quantitative approaches. Subjects in this study were teachers (Observer), researchers (practitioners), and grade IV students of SDN 23 Ujung Gurun as many as 27 people. The results of cycle I research on RPP gained an average percentage value of 76,78% (C), increasing in cycle II to 85,71% (B). The implementation of cycle I on teacher activity earned an average percentage value of 78,12% (C), increasing in cycle II to 87,5% (B). The implementation of cycle I on student activity earns an average percentage value of 78,12% (C), increasing in cycle II to 85,71% (B). Thus, it can be concluded that The Number Head Together Learning model can enhance the integrated thematic learning process in elementary school